MODEL KOREKSI GEOMETRI SISTEMATIK DATA IMAGER PUSHBROOM MENGGUNAKAN METODE PROYEKSI KOLINEAR [PUSHBROOM IMAGER DATA SYSTEMATIC GEOMETRIC CORRECTION MODEL USING COLLINEAR PROJECTION METHOD] - Hakim, Patria Rachman; Rahman, Abdul; Suhermanto; Rachhim, Elvira (Indonesian Journal of Aerospace, 2012)
LAPAN-A3 satellite, which is planned to be launched on 2014, will carry a 4 channels pushbroom imager. An image pre-processing is needed to assure that there will be no distortion on the output image data, particularly a systematic distortion, whether it is geometric or radiometric. Systematic geometric correction is intended to eliminate geometric distortion which are predictable such as view angle, earth curvature, earth rotation and varrying camera orientation during observation. The colinear projection method is used in order to transform every pixel on the image into earth coordinate points. Systematic geometric correction needs satellite ancillary data such as position and camera orientation from GPS and star sensor. This research simulated dummy data as substitute to distorted image and ancillary data for designing and simulation purpose. The simulation result shows that the systematic geometric correction algorithm is able to correct the distortion occured in image. A corrected image with 1000 meter accuracy can be achieved with 0,1 degree orientation data accuracy while 0,01 degree orientation data accuracy produces an even better 100 meter accuracy corrected image for nadir observation.